The Psychological Development of The Main Character of Becoming A Gang Leader through Frustration; Reflections on Dashnerâ€™s â€œThe Maze Runnerâ€ (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
In this study, the writer emphasized the psychological development of the main character reflected in the story. Then the main character must convince the other, there is a better place outside the Glade. Therefore, this study aims to analyze how the process of psychological developments of being a leader through frustration and to analyze how the main character shows an ability to lead. This is a qualitative study using psychoanalytic approach by Sigmund Freud. The writer collected the data relating to the psychological development from frustration to being a leader by using The Maze Runner novel. The secondary data were taken from some sources, such as books, dictionary, encyclopedia, and also articles related to this research. Meanwhile the procedures for collecting data were done by reading, identifying, inventorying, classifying, selecting and reporting. In conducting the study, Freudâ€™s psychoanalysis including id, ego, and superego are employed to reveal the main character frustration and shows the leadership ability in The Maze Runner. The findings of the analysis showed that; first, the causes of frustration are anxiety, hatred, and fear. It had been found that frustration was the results of the superego pressure that cannot be controlled by the ego. The frustration can be dangerous if the person who is frustrated does not fight against the pressure he gets. Second, there are seven leading ability which found in the novel such as having a purpose, curiosity, fairness, giving the suggestion, appreciates, and source of inspiration. Thomas is able to control the pressure from superego and his desire from id. He can make a good decision for his ego whether yielding his id or obey the superego. Then, he does not only focus on his frustration, but he can develop from frustration to be a good leader. Keywords: psychoanalysis, psychological development, leader, frustation, adolescent